PENEGAKAN HUKUM PENGGUNA NARKOTIKA DALAM PENCEGAHAN PENGULANGAN TINDAK PIDANA NARKOTIKA SETELAH REHABILITASI BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - M. Ewin Safrullah; Joko T. Suroso (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2022)
This study describes and examines Law Enforcement Against Narcotics Abuse so that there is no repetition after rehabilitation based on Law Number 35 of 2009 concerning Narcotics. Narcotics have long been a major concern of various countries, including Indonesia, because they have a broad impact that can weaken the foundations of the country. Indonesia is the fourth most populous country in the world after China, America and India, with such a large population, Indonesia has become an international share of various commodities, including the illicit trafficking of narcotics. This study uses a qualitative approach, observing the object under study as the main instrument in collecting and analyzing data. In its development, narcotics are abused not only in the context of treatment or religious rituals, but are used to get sensations for the body, which can cause dangers in the form of addiction that can damage the wearer's body and soul. Narcotics abusers according to Article 1 paragraph (15), Law No. 35 of 2009 concerning Narcotics, states that abusers are people who use narcotics without rights or against the law. The dangerous impact of Narcotics is very detrimental, giving the initiative of countries in the world including Indonesia by classifying it as a crime in the applicable legislation. Basically Narcotics have benefits, namely in the fields of medicine and science, so that they are used properly and provide legal protection to law enforcement officers to limit the use of Narcotics, so as to reduce the impact of the dangers of Narcotics.